First Methodist Episcopal church Ketchikan, Alaska, circa 1929-1930 - Unidentified
The first Methodist Episcopal church, Ketchikan was built in 1901. A rebuilt church stands today in the same location on 400 Main Street Ketchikan, AK. PH Coll 1331.3b